ความสัมพันธ์ระหว่างความฉลาดทางจิตวิญญาณ สติ และความสุขตามแนวทางพุทธศาสนา - รัตนเพชร(Sudarat Rattanaphet), สุดารัตน์; จิตต์จรัส(Niyada Chittcharat), นิยะดา; เพียซ้าย(Pinyapan Piasai), ภิญญาพันธุ์ (Journal of Behavioral Science for Development, 2016)
(The relationship among spiritual intelligence, mindfulness, and happiness in Buddhism) Abstract This research aimed at investigating the theoretical knowledge about the relationship among spiritual intelligence, mindfulness, and happiness in Buddhism. The study analyzed mediating and moderating variables to enhance understanding about the relationship among these variables more completely. A sample of 350 registered nurses from a government hospital participated in this study. They were drawn by stratified random sampling technique. The instruments for collecting data were questionnaires. Pearson’s correlation coefficient was used to analyze the relationship between two of variables. Baron and Kenny’s steps (1986) and bootstrap method were used to test indirect effects for mediation analysis whereas hierarchical multiple regression analysis was used for moderation analysis. The results were shown that spiritual intelligence was positively correlated with mindfulness. Both spiritual intelligence and mindfulness were positively correlated with happiness in Buddhism. Moreover, mindfulness was a partial mediator and moderator of the relationship between spiritual intelligence and happiness in Buddhism as well as spiritual intelligence was a partial mediator and moderator of the relationship between mindfulness and happiness in Buddhism. Keywords: spiritual intelligence , mindfulness , happiness in Buddhism